Tumor Necrosis Factor Receptor-Associated Factor 5 Interacts with the NS3 Protein and Promotes Classical Swine Fever Virus Replication - Lv, Huifang (Viruses, 2018)
Classical swine fever, caused by classical swine fever virus (CSFV), is a highly contagious and high-mortality viral disease, causing huge economic losses in the swine industry worldwide. CSFV non-structural protein 3 (NS3), a multifunctional protein, plays crucial roles in viral replication. However, how NS3 exactly exerts these functions is currently unknown. Here, we identified tumor necrosis factor receptor-associated factor 5 (TRAF5) as a novel binding partner of the NS3 protein via yeast two-hybrid, co-immunoprecipitation and glutathione S-transferase pull-down assays. Furthermore, we observed that TRAF5 promoted CSFV replication in porcine alveolar macrophages (PAMs). Additionally, CSFV infection or NS3 expression upregulated TRAF5 expression, implying that CSFV may exploit TRAF5 via NS3 for better growth. Moreover, CSFV infection and TRAF5 expression activated p38 mitogen activated protein kinase (MAPK) activity, and inhibition of p38 MAPK activation by the SB203580 inhibitor suppressed CSFV replication. Notably, TRAF5 overexpression did not promote CSFV replication following inhibition of p38 MAPK activation. Our findings reveal that TRAF5 promotes CSFV replication via p38 MAPK activation. This work provides a novel insight into the role of TRAF5 in CSFV replication capacity.